Women and the shaping of British Methodism Persistent preachers, 1807-1907. - Lloyd, Jennifer M. (Manchester : Manchester University Press, 2010)
A response to the prominent Methodist historian David Hempton?s call to analyse women?s experience within Methodism, this book is the first to deal with British Methodist women preachers over the entire nineteenth century. The author covers women preachers in Wesley?s lifetime, the reason why some Methodist sects allowed women to preach and others did not, and the experience of Bible Christian and Primitive Methodist female evangelists before 1850. She also describes the many other ways in which women supported their chapel communities. The book also includes discussion of the careers of mid-ce.
9780719078859; 9780719078859; Copyright; Contents; List of figures; Acknowledgements; Abbreviations; Introduction; 1. Women in eighteenth-century Methodism; 2. Women preachers' place in a divided Methodism; 3. The heyday of female itinerancy; 4. Philanthropists, volunteers, fund-raisers, and local preachers; 5. Women as Revivalists; 6. Women in missions at home and abroad; 7. Deaconesses, Sisters of the People, andthe revival of female itinerancy; Afterword; Bibliography; Index.
Description based on print version record.
Keywords: Geschichte 1807-1907.; Great Britain -- Church history -- 19th century; Methodist Church (Great Britain) -- Clergy -- History -- 19th century; Methodist women -- Great Britain -- History -- 19th century; Methodistische Kirche (Gro€britannien); Predigerin; Methodist Church (Great Britain) -- Clergy -- History -- 19th century; RELIGION / Christianity / Methodist; Electronic books